Examining Gen Z’s Intention to Join NFT Loyalty Programs: The Role of Perceived Value and Ease of Use - Mujiyanti, Sri Ayudha; Sudarmiatin (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to examine the influence of perceived value and perceived ease of use on Generation Z's intention to participate in NFT-based loyalty programs. Perceived value is measured through three key dimensions: functional value, symbolic value, and hedonic value, while perceived ease of use is tested as a moderating variable. A quantitative approach using PLS-SEM analysis was applied, with a saturated sample of 50 Gen Z respondents. The results show that perceived value has a significant positive effect on the intention to join NFT-based loyalty programs, while perceived ease of use does not significantly moderate this relationship. These findings suggest that businesses should focus more on delivering strong perceived value when designing NFT loyalty strategies, particularly in appealing to the preferences and digital experiences of Gen Z consumers.